Systems Genetics and Systems Biology Analysis of Paraquat Neurotoxicity in BXD Recombinant Inbred Mice. (6th May 2020) - Torres-Rojas, Carolina; Zhuang, Daming; Jimenez-Carrion, Paola; Silva, Isabel; O'Callaghan, James P; Lu, Lu; Zhao, Wenyuan; Mulligan, Megan K; Williams, Robert W; Jones, Byron C
Abstract: Paraquat (PQ) is an herbicide used in many countries, including the United States. It is also implicated as a risk factor for sporadic Parkinson's disease, especially in those living in agricultural areas and drinking well water. Studies linking PQ to sporadic Parkinson's disease are not consistent however and there appears to be interindividual differential susceptibility. One likely reason is genetically based differential susceptibility to paraquat neurotoxicity in subpopulations. To address this issue, we tested the effects of paraquat in a genetic reference population of mice (the BXD recombinant inbred strain family). In our earlier work, we showed that in genetically susceptible mice, paraquat increases iron in the ventral midbrain, the area containing the substantia nigra. Our hypothesis is that genetic variability contributes to diverse PQ-related susceptibility and iron concentration. To test this hypothesis, we treated male mice from 28 to 39 BXD strains plus the parental strains with 1 of 3 doses of paraquat, 1, 5, and 10 mg/kg 3 times on a weekly basis. At the end of the treatment period, we analyzed the ventral midbrain for concentrations of iron, copper, and zinc, also we measured the concentration of paraquat in cerebellum, and proinflammatory cytokines in serum and cerebellum. The effect on paraquat-treated mice with 5 mg/kg and principal component analysis of iron showed suggestive quantitative trait loci on chromosome 5. Overall, our results suggest that gene Prkag2 and related networks may serve as potential targets against paraquat toxicity and demonstrate the utility of genetically diverse mouse models for the study of complex human toxicity.